(untitled) (Research, Society and Development, 2022)
The present study aims to identify the main issues of intellectual production related to Forensic accounting and its dynamics in the period from 2000 to 2020, with the dynamics of the number of annual publications, the authors who published the most on the subject in the period and where these publications were carried out in the UFRJ and UFSC repositories. The subject of Forensic Accounting has been approached under different approaches in academic productions, such as, for example, accounting expertise in the judicial sphere, criminal accounting expertise, accounting expert report, among others. Considering that the subject of accounting expertise is important for interested parties, whether they are accountants and academics themselves for using it as a source of knowledge, or users being from the legal environment such as magistrates, lawyers and parties involved in legal proceedings. To achieve the objective, an exploratory, quantitative, and bibliometric research was designed. After carrying out the research in the institutional repositories of UFRJ and UFSC, 468 articles were found, being listed in order of relevance of the website itself. After analyzing them and choosing the articles, the 54 most relevant ones were chosen. Thus, it became evident that the accountant, that is, the accounting profession, is the link between expertise, the judiciary and accounting. Once the accounting expert provides, through the expertise applied in accounting, the information for decision making and resolution of conflicts of interest in litigation to the judiciary or by the interested parties.